Study of Bacterial Community Composition and Correlation of Environmental Variables in Rambla Salada, a Hypersaline Environment in South-Eastern Spain - Oueriaghli, Nahid; Castro, David J.; Llamas, Inmaculada; Béjar, Victoria; Martínez-Checa, Fernando (Frontiers in Microbiology, 2018)
We studied the bacterial community in Rambla Salada in three different sampling sites and in three different seasons and the effect of salinity, oxygen and pH. All sites samples had high diversity and richness (Rr>30). The diversity indexes and the analysis of dendrograms obtained by DGGE fingerprint after applying Pearson´s and Dice´s coefficient showed a strong influence of sampling season. The Pareto-Lorenz (PL) curves and Fo analysis indicated that the microbial communities were balanced and despite the changing environmental conditions, they can preserve their functionality. The main phyla detected by DGGE were Bacteroidetes (39.73%), Proteobacteria (28.43%), Firmicutes (8.23%) and Cyanobacteria (5.14%). The majority of the sequences corresponding to uncultured bacteria belonged to Bacteroidetes phylum. Within Proteobacteria, the main genera detected were Halothiobacillus and Roseovarius. The environmental factors which influenced the community in a higher degree were the salinity and oxygen. The bacteria belonging to Bacteroidetes and Proteobacteria were positively influenced by salinity. Nevertheless, bacteria related to Alpha- and Betaproteobacteria classes and phylum Firmicutes showed a positive correlation with oxygen and pH but negative with salinity. The phylum Cyanobacteria were less influenced by the environmental variables. The bacterial community composition of Rambla Salada was also studied by dilution-to-extinction technique. Using this method, 354 microorganisms were isolated. The 16S sequences of 61 isolates showed that the diversity was very different to those obtained by DGGE and with those obtained previously by using classic culture techniques. The taxa identified by dilution-to-extinction were Proteobacteria (81.92%), Firmicutes (11.30%), Actinobacteria (4.52%) and Bacteroidetes (2.26%) phyla with Gammaproteobacteria as predominant class (65.7%). The main genera were: Marinobacter (38.85%), Halomonas (20.2%) and Bacillus (11.2%). Nine of the 61 identified bacteria showed less than 97% sequence identity with validly described species and may well represent new taxa. The number of bacteria in different samples, locations and seasons were calculated by CARD-FISH, ranging from 54.3% to 78.9% of the total prokaryotic population.In conclusion, the dilution-to-extinction technique could be a complementary method to classical culture based method, but neither gets to cultivate the major taxa detected by DGGE. The bacterial community was influenced significantly by the physico-chemical parameters (specially the